The impact of the implementation of physician assistants in inpatient care: A multicenter matched-controlled study - Timmermans, Marijke J. C.; van Vught, Anneke J. A. H.; Peters, Yvonne A. S.; Meermans, Geert; Peute, Joseph G. M.; Postma, Cornelis. T.; Smit, P. Casper; Verdaasdonk, Emiel; de Vries Reilingh, Tammo S.; Wensing, Michel; Laurant, Miranda G. H. (PLOS ONE, 2017)
Background Medical care for admitted patients in hospitals is increasingly reallocated to physician assistants (PAs). There is limited evidence about the consequences for the quality and safety of care. This study aimed to determine the effects of substitution of inpatient care from medical doctors (MDs) to PAs on patients’ length of stay (LOS), quality and safety of care, and patient experiences with the provided care. Methods In a multicenter matched-controlled study, the traditional model in which only MDs are employed for inpatient care (MD model) was compared with a mixed model in which besides MDs also PAs are employed (PA/MD model). Thirty-four wards were recruited across the Netherlands. Patients were followed from admission till one month after discharge. Primary outcome measure was patients’ LOS. Secondary outcomes concerned eleven indicators for quality and safety of inpatient care and patients’ experiences with the provided care. Results Data on 2,307 patients from 34 hospital wards was available. The involvement of PAs was not significantly associated with LOS (β 1.20, 95%CI 0.99–1.40, p = .062). None of the indicators for quality and safety of care were different between study arms. However, the involvement of PAs was associated with better experiences of patients (β 0.49, 95% CI 0.22–0.76, p = .001). Conclusions This study did not find differences regarding LOS and quality of care between wards on which PAs, in collaboration with MDs, provided medical care for the admitted patients, and wards on which only MDs provided medical care. Employing PAs seems to be safe and seems to lead to better patient experiences. Trial registration ClinicalTrials.gov Identifier: NCT01835444